Os efeitos das transferências intergovernamentais das finanças públicas municipais brasileiras - Almeida, Renata Neri de (2014)
The Brazilian Constitution of 1988 made several changes in the Brazilian fiscal federalism. The municipalities were recognized as federal entities, assuming greater responsibilities in the provision of public local services. However, the municipalities financial strengthening was based more in the increasing of the vertical constitutional transfers than by expanding its tax base. Intergovernmental transfers have assumed a significant role in the Brazilian federative relations system, making it an essential item in the revenue for most municipalities. Several studies argue that transfers tend to be spent in public local services in a much bigger way than the local private revenues. Funds received via transfers tend to be used to increase public spending rather than being passed on to citizens (through tax cuts) in order to increase the local private goods consumption. This phenomenon is known as flypaper effect. This study therefore seeks to assess the occurrence of the flypaper effect in Brazilian municipalities between 2002 and 2010, using panel data for the set of 5,507 municipalities. It is used three econometric methods, ordinary least squares (OLS); fixed effects estimation (FE) and random effects estimation (RE). This work aims to overcome some shortcomings of previous studies, seeking to identify the flypaper effect not only in the total municipalities' expenditures, but also in specific municipalities spending. The results confirm the existence of this effect in Brazilian municipal finances (this effect, however, is more evident on current spending than on capital one). It is also observed the predominance of this effect regarding tax revenue, indicating that the transfer has not been used to increase private goods consumption by the citizens through tax cuts.